ANALYSIS CUSTOMER SATISFACTION LEVEL USING THREE-FACTOR THEORY AND REVISED IMPORTANCE-PERFORMANCE ANALYSIS IN EVERGLAM AESTHETIC CENTER - Hutagaol, Jesica; Basri, Mursyid Hasan (Journal of Business and Management, 2017)
Abstract. The amount of women from teenagers until adults need to look beautiful and perfect, provide an opportunity for the beauty and care industry. This fact drives the various industry engaged in the field of beauty and care growth in Indonesia. Therefore, Everglam Aesthetic Center is one of the beauty industry that growing now. Everglam Aesthetic Center tagline is: It’s the Place to Get Your Infinite Beauty, which provide a comprehensive service to customers need to know which attributes more increase on the level of customers satisfaction and importance in order to provide better service quality. The purpose of this research is to measure, analyze and increase attributes service quality that related to customer satisfaction in Everglam Aesthetic Center and then propose some recommendations of improvement. The literature review that needed in this research is related to service quality, customer satisfaction, SERVQUAL, three-factor theory of customer satisfaction and revised importance – performance analysis.The result finding from the data analysis in Everglam Aesthetic Center, it can be concluded that customer are tend to be satisfied enough with the fulfillment of basic factor, excitement factor and performance factor using three-factor theory analysis. There are 14 attributes that classified into basic factor, 2 attributes that classified into excitement factor and 2 attributes that classified into performance factor. While based on IPA grid result, Everglam Aesthetic Center need to improve the attributes in Quadrant IV named as Concentrate Here because these attributes is importance, but the performance low.Keywords: Everglam Aesthetic Center, Service Quality, Three-Factor Theory of Customer Satisfaction, Revised Importance-Performance Analysis